Faktor yang Berhubungan dengan Kualitas Hidup Orang dengan HIV/AIDS (Odha) - Ade Jovi Purukan; Jilly Toar; Nancy S. Bawiling (Jurnal Ilmiah Kesehatan, 2025)
This study aims to analyze the factors related to the quality of life of People with HIV/AIDS (PLWHA) at the VCT Clinic of Anugerah Tomohon Hospital in 2022. The research design used was cross-sectional with a quantitative observational-analytic approach. Data were collected through the WHOQOL-HIV-BREF questionnaire and analyzed using the Chi Square test to assess the relationship between duration of HIV and quality of life. Respondents in this study consisted of 30 PLWHA, with the majority of respondents being male (73.3%), and the largest age range was 20-30 years (53.3%). The results showed that 50% of PLWHA had a good quality of life, while the other 50% had a poor quality of life. There was no significant relationship between the duration of HIV and the quality of life of PLWHA (P Value = 0.713). Factors such as social support, stigma, and depression may play a role in the quality of life of PLWHA. This study is expected to provide insight to improve the quality of health services for PLWHA, as well as assist in the prevention and management of HIV/AIDS in Indonesia.